Construction of Enterprise Logistics Decision Model Based on Supply Chain Management - Tippayawong, Korrakot Yaibuathet (International Journal of Informatics and Information Systems, 2023)
In the logistics decision-making of supply chain management, both professional logistics enterprises and enterprises that need to use the logistics system are pursuing efficient, low-cost, convenient and fast business model and effective management methods. Firstly, the paper analyzes the development background, importance, feasibility and necessity of supply chain management, and formulates the classification summary from customer relationship management, supplier relationship management and internal manufacturing process of supply chain. This paper analyzes the importance of supply chain management. Combined with the future development trend, the importance and urgency of theory and application are analyzed. Then it introduces the important relationship of logistics decision-making in supply chain management and its development status. In the study of logistics distribution optimization decision-making mechanism based on supply chain management, this paper establishes the optimization decision-making model, formulates the decision- making principles, analyzes and evaluates the decision-making conditions, and determines the logistics decision-making objectives.